Metastatic Adenocarcinoma of Mandible with Unknown Primary Origin (CUP Syndrome): A Rare Case Report - Saede Atarbashi-Moghadam; Mohammad Jafarian; Shaghayegh Dowdani (Shiraz University of Medical Sciences, 2023)
Metastatic lesions of the jaws are a diagnostic challenge because of their scarcity and uncharacteristic clinical-radiographic features. Carcinoma of unknown primary origin (CUP) is characterized by the existence of metastatic disease with no recognized primary neoplasm after a comprehensive work-up. CUP shows a poor prognosis with limited treatment choices. This paper presents a 64-year-old male with a chief complaint of paresthesia of the chin and lower lip. Panoramic radiography showed an ill-defined radiolucency in the left mandibular molar area and the residue of the first molar root. Microscopic examination demonstrated features of mucin-producing adenocarcinoma and was not similar to common neoplasms of the jaw. The whole-body scan revealed multiple osseous uptakes. CDX2 was diffusely positive. However, in the end, the origin of the primary tumor was not determined. Considering the aforementioned data, the diagnosis of metastatic adenocarcinoma with unknown primary origin was made. CUP of the oral cavity is an extremely rare event. The possibility of metastasis should be raised in a patient who complains of paresthesia. Awareness of the clinical and histopathologic features of these malignancies is crucial for clinicians and pathologists to have a proper diagnosis.